Automatic feedback of fencing specific movements through wearable sensor technology - Lee, Nitasha Yen Lin (2019)
Fencing is a high intensity sport which requires explosive movements such as the Lunge and the Flèche throughout a competition. Competitive fencing has been progressing significantly over the past decade. With this growing interest in fencing, there is a need for improved training methods and wearable sensor technology holds a promise for this application. The objective of this research project is to monitor fencing specific movements and training workloads. With the knowledge of training workloads, it would provide coaches and fencers with a better understanding on periodising a plan for maximising performance and to reduce the risk of injuries.